2014
DOI: 10.3109/09638288.2014.892636
|View full text |Cite
|
Sign up to set email alerts
|

Lost in translation: exploring therapists’ experiences of providing stroke rehabilitation across a language barrier

Abstract: As it appears rehabilitation is affected by a language barrier, this is likely to impact on the outcome of an individual's rehabilitation. The concept of "subtle communication" should be recognised as a vital component of therapeutic skills. Improving access to formal interpreters, extending their role and introducing training could reduce practical barriers. The conceptual model could be utilised by clinicians as a tool for reflection or education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…When using in-person interpreters, aligning the schedules of the physician, professional interpreter and patient is frequently complex, with some physicians commenting that it can range from several hours to days before these sessions occur. This is confirmed by the findings from other researchers working with physicians and other healthcare practitioners 31 32. As a result, it is not surprising that in some circumstances, physicians opt for the ‘path of least resistance’ (which may include using another healthcare professional or a family member to interpret).…”
Section: Discussionsupporting
confidence: 63%
“…When using in-person interpreters, aligning the schedules of the physician, professional interpreter and patient is frequently complex, with some physicians commenting that it can range from several hours to days before these sessions occur. This is confirmed by the findings from other researchers working with physicians and other healthcare practitioners 31 32. As a result, it is not surprising that in some circumstances, physicians opt for the ‘path of least resistance’ (which may include using another healthcare professional or a family member to interpret).…”
Section: Discussionsupporting
confidence: 63%
“…Alternatively, clinicians must understand individual preferences and expectations to determine how the patient will receive, interpret, and share health information (Beach, Saha, & Cooper, 2006). Good communication strengthens trust and the therapy relationship, facilitating patient engagement in shared decision-making, a key component of patience-centered care (Elwyn et al, 2012; Taylor & Jones, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…This lack of information on therapy tasks is perhaps a reflection that speech pathologists are potentially engaging professional interpreters more frequently for assessment sessions (Roger et al . ) and conducting fewer therapy sessions with CALD adults with ACDs (Taylor and Jones ), despite recommendations that CALD adults should be treated by collaborating with professional interpreters (ASHA n.d., Lorenzen and Murray ). Moreover, speech pathology therapy involving professional interpreters is likely still in the early stages of research.…”
Section: Discussionmentioning
confidence: 99%
“…While the reasons behind the difficulties in the availability and accessibility of professional interpreters were not specified, possible reasons have been raised in other literature. This includes a shortage of professional interpreters for particular languages, for example, Australian Indigenous languages (in some regions of Australia) or less commonly spoken languages/dialects (Commonwealth Ombudsman , Taylor and Jones ). Moreover, the review identified that speech pathologists were also concerned about the limited time to brief and prepare materials with professional interpreters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation